Comparison of Vitamin D Levels in Children with Recurrent Respiratory Tract Infections with Normal Children - Zaman, Saeed; Ahmed, Umama; Shah, Sajid Ali; Munir, Misbah; Nawaz, Sadaf; Goheer, Lutfullah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare Vitamin D levels in children with recurrent respiratory tract infections with normal children.Study Design: Case-control study.Place and Duration of Study: Department of Paediatrics, Combined Military Hospital, Kharian, from Nov 2018 to Dec 2019.Methodology: Sixty children fulfilling the inclusion criteria from the indoor department of Paediatrics, Combined Military Hospital, Kharian were included in the study. Thirty patients were in the recurrent respiratory tract infections-group (cases), while 30 were in the normal children- group (control). The blood sample was drawn from all the children included in the study to analyze serum 25 (OH) D levels. Data regarding Vitamin D levels were noted from both groups as per operational definition on an especially designed proforma.Results: The mean age of cases was 5.63 ± 2.82 years, and controls were 5.66 ± 2.44 years. In cases-group, 20 (66.7%) cases had low vitamin D levels, and 10 (33.3%) cases had normal vitamin D levels, while in control subjects, 11 (36.7%) children had low vitamin D levels and 19 (63.3%) children had average vitamin D level. Cases with low vitamin D levels were statistically higher than controls, with the p-value of 0.02 with a significant odds ratio = 3.455 (95% CI: 1.95–9.99).Conclusion: This study concludes that children with recurrent respiratory tract infections had low vitamin D levels compared with normal children.